STUDY ON PRODUCTION POTENTIAL AND PRESERVATION METHODS OF HIDE AND SKIN IN THREE SELECTED DISTRICTS OF GAMBELLA REGION, SOUTH WEST ETHIOPIA - Fereja, Getachew Bekele; Lamaro, Merhun; Berhe, Genet; Berhe, Aregay (International Journal of Research -GRANTHAALAYAH, 2017)
Ethiopia is believed to have the largest livestock population in Africa. An estimate indicates that the country is a home for about 54 million cattle, 25.5 million sheep and 24.06 million goats. Therefore, this study was conducted in three selected districts of Gambelia regional state with the objective to assess the production potentials and preservation methods of hide and skin. As a secondary product of the meat consumption, the supply of hides & skins depends on the demand for meat, the rearing, management and slaughtering of animals, with little response to change in price and demand for the products. Hides and skins could be obtained from fish, birds and reptiles as well as wild and domesticated animals. The sample size of the study was estimated to be 384 (128 from Gambella zuria, 128 from Godare and 128 from Lare) using the formula stated in Thrust field. The quantitative data was organized, summarized and encoded on excel sheet and analyzed with the help of Statistical Analysis System (SAS) 9.2 version 2008.Qualitative data derived from direct observations and key informants was examined and presented in form of discussions. In the study areas, for all the three species, the mean annual slaughter at household level ranges between 0.07,1.66 and 1.73 cattle, sheep and goat annually, respectively in the study area. Of the 384 respondents interviewed, (94.01%) used the preservation methods of ground air dry and 6.25% use salt preservation for hide and skin preservation, respectively. Generally, production potential and preservation methods variations were observed among the Hide and skin producers, which suggest that there is an opportunity for improvement through awareness creation.